Ethiopia Strategy Support Program (ESSP) - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
The Ethiopia Strategy Support Program II (ESSP II) website is a medium for circulating information relevant to Ethiopia's agriculture policy and strategy development. The blog contains updates on ESSP's work - ongoing research, upcoming events, publications, findings - as well as general information to support agricultural researchers and policymakers.